2016
DOI: 10.9790/0853-150724246
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Concentration Techniques for Detection of Intestinal Parasitic Infections – to Evaluate the Prevalence And to Identify A Better Method of Concentration Technique At A Tribal Tertiary Care Hospital

Abstract: Parasitic infection caused by helminths and protozoa are the major cause of human disease in most countries of tropical region. It is estimated that about 3.5 billion people are infected with intestinal parasites of whom 450 million are ill. The prevalence of intestinal parasitic infection varies not only geographically but also in different region in the same country. The present study is undertaken to determine the rate of prevalence of intestinal parasitic infection among all age group of people in this tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
3
1
1
Order By: Relevance
“…As far as the detection rates for the two techniques used, it was obvious that the detection rate (24.6%) was reported for the formal ether concentration technique and 23% for the wet preparation, which indicates that both techniques have the same efficacy in detecting intestinal parasites. Our results, for the formal ether technique does not agree with Venkatesh (2016) [12] ,…”
Section: Discussioncontrasting
confidence: 91%
“…As far as the detection rates for the two techniques used, it was obvious that the detection rate (24.6%) was reported for the formal ether concentration technique and 23% for the wet preparation, which indicates that both techniques have the same efficacy in detecting intestinal parasites. Our results, for the formal ether technique does not agree with Venkatesh (2016) [12] ,…”
Section: Discussioncontrasting
confidence: 91%
“…However, a study from Hyderabad suggested that formal ether sedimentation techniques had increased the prevalence rates when compared to direct microscopic methods. 12 In our study, direct microscopic methods were used which may be one of the reasons for the low prevalence of IPI.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal evaluations were performed for each rat using a normal saline Lugol's iodine smear seven days after infection for three days to confirm the infection of the rats. To count the G. lamblia cysts after the last treatment dosage, 1 g of the stool samples was collected on three consecutive days using a hemocytometer to determine the mean number of cysts/HPF in the stained smears [21].…”
Section: Assessment Of the Efficacy Of The Treatment 261 Parasitologi...mentioning
confidence: 99%